National Geographic guide to medicinal herbs : the world's most effective healing plants - Johnson, Rebecca L.; Foster, Steven; Weil, Andrew; National Geographic Society (Washington, D. C. : National Geographic, 2010)
A resource organized by body system lists the key herbal remedies available, their uses, and cautionary advice, in a book that includes full-color photos, a glossary and several thematic indexes.
Includes index.
Keywords: Materia medica, Vegetable; Herbs -- Therapeutic use; Plants, Medicinal